The oral care practice in preventing clinical pulmonary infection on ventilated patients in intensive care unit: a retrospective study / Norliza Zahri and Noraini Hashim - Zahri, Norliza; Hashim, Noraini (Faculty of Health Sciences, 2019)
Ventilator-associated pneumonia (VAP) is a dangerous infection in the oropharyngeal cavity. It is one of the most common healthcare-associated infections especially for patients who admitted in Intensive Care Units (ICU). The Oral care practice is a procedure in maintaining the healthcare of the oral cavity for ventilated patients in preventing Ventilator Associated Pneumonia. This study is to determine the incidence of VAP on ventilated patient in ICU. Patients in the ICU received oral care practice with chlorohexidine 0.12% or toothbrushing with chlorohexidine 0.12% as a routine practice. The result of VAP was assessing using data from the Clinical Pulmonary Infection Score (CPIS) be a predictor of VAP outcome. To identify the Relationship between oral care practice and Clinical Pulmonary Infection Score (CPIS) on ventilated patients in ICU. This is a Retrospective Study, whereby the researcher interested in a present outcome and attempts to determine antecedent factors that caused for it. Intensive Care Unit, Kuantan Medical Center, Pahang Darul Makmur. A Purposive sampling was used to patient who meet the eligibility; forty were randomly assigned on patient with mechanical ventilation. Totally, 38 subjects were included in the data analyses. The Ventilator Associated Pneumonia was evaluated by the Clinical Pulmonary Infection Score (CPIS) for baseline monitoring during admission and three days after the oral care practice done. Chi-square test was done for the second objective. There is no-significant difference on relationship of oral care practice and Clinical Pulmonary Infection Score (CPIS). These results have been supported by similar studies. This finding suggest that application of oral care intervention can prevent the ventilator associated-pneumonia during hospitalization of patients.